Activation of Transient Receptor Potential Vanilloid 4 Impairs the Dendritic Arborization of Newborn Neurons in the Hippocampal Dentate Gyrus through the AMPK and Akt Signaling Pathways - Tian, Yujing; Qi, Mengwen; Wang, Zhouqing; Wu, Chunfeng; Sun, Zhen; Li, Yingchun; Sha, Sha; Du, Yimei; Chen, Lei; Chen, Ling (Frontiers in Molecular Neuroscience, 2017)
Neurite growth is an important process for the adult hippocampal neurogenesis which is regulated by a specific range of the intracellular free Ca2+ concentration ([Ca2+]i). Transient receptor potential vanilloid 4 (TRPV4) is a calcium-permeable channel and activation of it causes an increase in [Ca2+]i. We recently reported that TRPV4 activation promotes the proliferation of stem cells in the adult hippocampal dentate gyrus (DG). The present study aimed to examine the effect of TRPV4 activation on the dendrite morphology of newborn neurons in the adult hippocampal DG. Here, we report that intracerebroventricular injection of the TRPV4 agonist GSK1016790A for five days (GSK1016790A-injected mice) reduced the number of doublecortin immunopositive (DCX+) cells and DCX+ fibers in the hippocampal DG, showing the impaired dendritic arborization of newborn neurons. The phosphorylated AMP-activated protein kinase (p-AMPK) protein level increased from 30 min to 2 h, and then decreased from 1 to 5 d after GSK1016790A injection. The phosphorylated protein kinase B (p-Akt) protein level decreased from 30 min to 5 d after GSK1016790A injection; this decrease was markedly attenuated by the AMPK antagonist compound C (CC), but not by the AMPK agonist AICAR. Moreover, the phosphorylated mammalian target of rapamycin (mTOR) and p70 ribosomal S6 kinase (p70S6k) protein levels were decreased by GSK1016790A; these changes were sensitive to 740 Y-P and CC. The phosphorylation of glycogen synthase kinase 3β (GSK3β) at Y216 was increased by GSK1016790A, and this change was accompanied by increased phosphorylation of microtubule-associated protein 2 (MAP2) and collapsin response mediator protein-2 (CRMP-2). These changes were markedly blocked by 740 Y-P and CC. Finally, GSK1016790A-induced decrease of DCX+ cells and DCX+ fibers was markedly attenuated by 740 Y-P and CC, but was unaffected by AICAR. We conclude that TRPV4 activation impairs the dendritic arborization of newborn neurons through increasing AMPK and inhibiting Akt to inhibit the mTOR-p70S6k pathway, activate GSK3β and thereby result in the inhibition of MAP2 and CRMP-2 function.